International Political Risk Management : The Brave New World - Moran, Theodore H. (Washington, DC: World Bank and Multilateral Investment Guarantee Agency, 2013)
Part One provides a first look from the "supply side" at the reaction of the political risk insurance market to September 11, 2001, the Argentine economic crisis, and other recent corporate upheavals. This section starts off with the public provider's perspective, provided by Vivian Brown, Chief Executive of the U.K.'s Export Credits Guarantee Department (ECGD) and President of the Berne Union. Part Two explores the reactions of investors and lenders to the recent upheavals in the global economy. It pays particular attention to the problems confronting large infrastructure projects, in which purchase agreements are guaranteed by the host country, and revenues are denominated in local currency. It examines how political risk insurance can help lenders to return to financing infrastructure development in emerging markets, and asks to what extent investors and lenders need new products or new kinds of coverage to deal with currency crises. Part Three brings together Felton "Mac" Johnston, President, FMJ International Risk; Charles Berry, Chairman, Berry, Palmer & Lyle Limited; and Witold Henisz and Bennet Zelner, Assistant Professors at Wharton and Georgetown University respectively. Additional commentary is provided by David Bailey, Vice President, Sovereign Risk Insurance Ltd. and Edith Quintrell, Manager, Insurance, at the Overseas Private Investment Corporation, who provide perspectives on how the political risk insurance industry might evolve to meet the needs of insurers and reinsurers, on the one hand, and investors and lenders, on the other.